Avoidance Coping Partially Accounts for the Relationship Between Trauma-Related Shame and PTSD Symptoms Following Interpersonal Trauma - Tipsword, Jordyn M. (Violence against women, 2022)
Research has demonstrated that individuals experiencing trauma-related shame exhibit greater posttraumatic stress disorder (PTSD) symptoms. However, little research has investigated additional factors relevant to the shame–PTSD relationship. The current study examined the role of avoidance and approach coping in accounting for the trauma-related shame–PTSD association among 60 women who had experienced interpersonal trauma. Indirect effects tests revealed that avoidance coping partially accounted for the association between shame and interviewer-assessed PTSD symptoms, β = .21, SE = 0.08, 95% confidence interval (CI) = [0.03, 0.36]. These findings offer a novel contribution to the growing literature examining negative outcomes following interpersonal trauma.